VIOLATION OF THE RHEOLOGICAL PROPERTIES OF BLOOD IN PATIENTS WITH TYPE II DIABETES WITH DIABETES MACROVASCULAR - Tatiana Petrovna Bondar; Sergey Andreevich Petrovsky (Вестник Северо-Кавказского федерального университета)
The article presents the results of a survey of 55 people. It is established, that in diabetic patients, the decrease of the yield strength of the blood in the independence of the presence of vascular complications. Rheological changes of blood in the development of diabetic angiopathies connected with the biophysical properties of the cell membrane of red blood cells.